The new FIGO 2023 staging reclassification of patients with FIGO 2009 Stage IVB endometrial cancer correlates to progression-free and overall survival outcomes - Monal Garg; Priya Bhati; Pranidha Shree CA; Wesley M. Jose; Sheejamol V.S.; Keechilat Pavithran (Gynecologic Oncology Reports)
Objective: This study aims to determine the oncological outcomes of Stage IVB (FIGO 2009) Endometrial cancer patients and its comparison with the new (FIGO 2023) staging. Methods: A Retrospective analysis was conducted between May 30, 2011, and December 30, 2020 on all patients with stage IVB (FIGO 2009 Staging) endometrial cancer. Overall survival (OS) was the primary outcome. Progression-Free Survival (PFS) and comparison with new staging FIGO 2023 were the secondary outcomes. Kaplan-Meier curves and log-rank tests were used to compare the average OS time and PFS between the groups. Results: Fifty-one patients with Stage IVB endometrial cancer (2009 FIGO Staging) were included. Median age was 68 years. Serous histology was found in 24 (47.1 %) patients. After a median follow-up period of 24 months, median OS was 36 months and median PFS was 15 months. FIGO 2023 staging criteria reclassified the stages of 23 patients (45 %). Patients were restaged into Stage IIIB2 (9.8 %), IVA (5.8 %), IVB (55 %) and IVC (29.4 %). Median OS and PFS were not reached for stages IIIB and IVA, while the median OS and median PFS for stage IVB were 36 months and 18 months, respectively. However, patients with stage IVC had lower median OS and PFS of 10 months and 4 months, respectively. Conclusion: The clinical outcomes of patients with Stage IVB are varied depending mainly on the disease distribution. Patients with abdominal or pelvic disease had better survival outcomes and therefore, needed a different categorisation. Thus, FIGO 2023 Staging considers this varied disease distribution and appears to be a better prognostic indicator for this group.